(untitled) (International journal of artificial intelligence, 2025)
Particular attention is paid to ensuring the necessary level of collection of taxes and other mandatory payments in the Republic of Uzbekistan, radical improvement of services on the basis of cooperation between large taxpayers, tax administration and tax obligations. In the Address of the President of the Republic of Uzbekistan Sh.M.Mirziyoev to the Oliy Majlis dated December 28, 2018, “one should be interested in the timely payment of taxes, not tax evasion. The new version of the Tax Code should provide incentives for honest taxpayers, who are the backbone of the country's development, and punish those who operate in secret. It is necessary to reduce the tax burden, introduce a fair tax regime for all, and gradually abolish tax benefits. " is one of the important tasks in this regard.